GM‐CSF and uPA are required for Porphyromonas gingivalis‐induced alveolar bone loss in a mouse periodontitis model. Issue 8 (10th March 2015) - Lam, Roselind S; O'Brien‐Simpson, Neil M; Hamilton, John A; Lenzo, Jason C; Holden, James A; Brammar, Gail C; Orth, Rebecca K; Tan, Yan; Walsh, Katrina A; Fleetwood, Andrew J; Reynolds, Eric C
Abstract : Granulocyte‐macrophage colony‐stimulating factor (GM‐CSF) and urokinase‐type plasminogen activator (uPA) can contribute to the progression of chronic inflammatory diseases with possible involvement of macrophages. In this study, we investigated the role of both GM‐CSF and uPA in Porphyromonas gingivalis ‐induced experimental periodontitis using GM‐CSF−/− and uPA−/− mice. Intra‐oral inoculation of wild‐type (WT) C57BL/6 mice with P. gingivalis resulted in establishment of the pathogen in plaque and a significant increase in alveolar bone resorption. The infected mice also exhibited a CD11b + CD86 + macrophage infiltrate into the gingival tissue, as well as P. gingivalis ‐specific pro‐inflammatory cytokine and predominantly IgG2b antibody responses. In comparison, intra‐oral inoculation of P. gingivalis did not induce bone resorption and there was significantly less P. gingivalis recovered from plaque in GM‐CSF−/− and uPA−/− mice. Furthermore, P. gingivalis did not induce a macrophage gingival infiltrate or activate isolated peritoneal macrophages from the gene‐deficient mice. Pro‐inflammatory P. gingivalis ‐specific T‐cell cytokine responses and serum interferon‐gamma (IFN‐γ) and IgG2b concentrations were significantly lower in GM‐CSF−/− mice. In uPA−/− mice, T‐cell responses were lower but serum IFN‐γ and IgG2b levels were comparable with WT mice levels. These results suggest that GM‐CSF and uPA are both involved in the progression of experimental periodontitis, possibly via a macrophage‐dependent mechanism(s).